2014
DOI: 10.1558/calico.v32i1.25961
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Technology Acceptance Model (TAM) to explore the effects of a Course Management System (CMS)-Assisted EFL writing instruction

Abstract: This study illustrates a teaching model that utilizes a Blackboard (Bb) course management system (CMS) to support English writing instruction. It was implemented in a blended English research paper (RP) writing course, with specific learning resources and activities offered inside and outside the Bb CMS. A quasi-experimental study in which the results of two academic years were analysed is presented. The results showed that the experimental group significantly outperformed the control group in their final draf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…PU reflects the expected benefits from using the new technology, while PEOU reflects the perceived behavioral attitude in the theory of planned behavior (Davis, 1989). Researchers have made various claims on how PU and PEOU are often determined by a perceived attitude towards technology (Gangwar, Date, & Raoot, 2014;Gao & Bai, 2014); cognitive ability (Chen, Liu, Li, & Yen, 2013); social, cultural, and political influences (Kaushik & Rahman, 2015;Patsiotis, Hughes, & Webber, 2013); self-efficacy (Teoh, Siong, Lin, & Jiat, 2013); facilitating conditions (Chen & Chan, 2013;Tsai, 2015); usability measurement attributes used (Hsiao & Tang, 2015); and effectiveness, efficiency, learnability, and memorability (Chen & Chan, 2013). Kanjwani and Singh (2014) explored some of these external variables of TAM and found that perceived enjoyment, excitement and satisfaction are determinants of TAM.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…PU reflects the expected benefits from using the new technology, while PEOU reflects the perceived behavioral attitude in the theory of planned behavior (Davis, 1989). Researchers have made various claims on how PU and PEOU are often determined by a perceived attitude towards technology (Gangwar, Date, & Raoot, 2014;Gao & Bai, 2014); cognitive ability (Chen, Liu, Li, & Yen, 2013); social, cultural, and political influences (Kaushik & Rahman, 2015;Patsiotis, Hughes, & Webber, 2013); self-efficacy (Teoh, Siong, Lin, & Jiat, 2013); facilitating conditions (Chen & Chan, 2013;Tsai, 2015); usability measurement attributes used (Hsiao & Tang, 2015); and effectiveness, efficiency, learnability, and memorability (Chen & Chan, 2013). Kanjwani and Singh (2014) explored some of these external variables of TAM and found that perceived enjoyment, excitement and satisfaction are determinants of TAM.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…These involved concordancing activities [6] and the modeling of academic texts [7,9,23,32,47]. A concern with metacognitive self-regulation guided the remaining studies, two of which involve grammatical accuracy [4,5], one reflective scaffolding [11] one translation commentary [37] and one technology acceptance [41].…”
Section: Written Languagementioning
confidence: 99%
“…Beginning with the predominant written language paradigm, a closer inspection of the 24 AL2 studies that focus specifically on presentational writing skills reveals that 13 involve collaborative composition activities [3,13,14,19,22,24,27,29,30,36,39,40,43] 3 and 11 individual writing exercises [4,5,6,7,9,11,23,32,37,41,47].…”
Section: Written Languagementioning
confidence: 99%
“…), but without any corroborating evidence. In the remaining 26 studies [1,3,4,5,6,9,13,14,18,19,20,22,23,25,26,29,30,32,36,38,40,41,42,43,44,45], the competency level of students can only be determined based on circumstantial evidence (e.g. graduating L2 majors, students in an AL2 graduate course, etc.).…”
Section: Student Language Competency Levelmentioning
confidence: 99%